1990
DOI: 10.1136/bmj.300.6739.1548
|View full text |Cite
|
Sign up to set email alerts
|

Purpura and dermal thinning associated with high dose inhaled corticosteroids.

Abstract: Objective-To assess the effect of high dose inhaled corticosteroids on skin.Design-Cross sectional study of patients receiving treatment for chest diseases.Setting-Outpatient chest clinic in a teaching hospital.Patients-68 Patients divided into four groups of similar age-namely, 15 receiving long term oral prednisolone, 21 receiving high dose inhaled corticosteroids, 15 receiving low dose inhaled corticosteroids, and 17 controls.Main outcome measures-Skin thickness at three sites measured by A scan ultrasound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
81
2

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(85 citation statements)
references
References 22 publications
2
81
2
Order By: Relevance
“…In that study, a slight dermal thinning on the forearm was observed after treatment with daily budesonide doses of 800 -1600 g. The skin thickness was, however, normalized after 1-2 y of continuous therapy suggesting no dose relationship and only a temporary effect on the skin. Advanced dermal thinning and purpura are well known side-effects of treatment with oral corticosteroids and also with high-dose ICS (2)(3)(4). In an observational study in 157 children treated for 3-6 y with an average daily dose of ϳ500 g of budesonide, no skin bruising was reported in comparison with 111 control children (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that study, a slight dermal thinning on the forearm was observed after treatment with daily budesonide doses of 800 -1600 g. The skin thickness was, however, normalized after 1-2 y of continuous therapy suggesting no dose relationship and only a temporary effect on the skin. Advanced dermal thinning and purpura are well known side-effects of treatment with oral corticosteroids and also with high-dose ICS (2)(3)(4). In an observational study in 157 children treated for 3-6 y with an average daily dose of ϳ500 g of budesonide, no skin bruising was reported in comparison with 111 control children (22).…”
Section: Discussionmentioning
confidence: 99%
“…However, ICS may have systemic effects. High doses of ICS may result in purpura and dermal thinning (2,3). In older subjects, e.g.…”
mentioning
confidence: 99%
“…Skin bruising and thinning have been documented as side effects of ICS use [134][135][136], especially in patients receiving high-dose ICS [134]. There is a greater risk of easy bruising in elderly patients [135][136][137][138][139] and in women [135].…”
Section: Skin Thinning and Bruisingmentioning
confidence: 99%
“…118,119 One study showed that skin thickness measured by an ultrasound scan was significantly reduced by 15-19% in subjects on BDP 1000-2250 µg/day compared with controls. 118 In addition, the prevalence of bruising was significantly higher at 48% in this patient population compared with 12% in the control population. 118 The results of a further survey also indicated that easy bruising was the commonest reported symptom, with the use of ICS occurring in almost half of the individuals.…”
Section: Adverse Eventsmentioning
confidence: 99%